Acute respiratory failure due to Aspergillus niger infection with acute fibrinous and organazing pneumonia: A case report. (2022) - Okamura, Ken; Noro, Rintaro; Fujita, Kazue; Kure, Shoko; Kunugi, Shinobu; Takano, Hitoshi; Miyashita, Ryota; Tozuka, Takehiro; Tanaka, Toru; Sugano, Teppei; Sakurai, Yumi; Suzuki, Ayana; et al.
Abstract: A 59-year-old woman complaining of wet cough, hemoptysis, slight fever, anorexia, and malaise was admitted to hospital with suspected lobar pneumonia. She received treatment for myocardial infarction and deep venous thrombosis caused by familial protein C deficiency. Rapid deterioration due to respiratory failure occurred despite intensive care with broad-spectrum antibiotics. At a later date, sputum examination revealed the presence of Aspergillus niger . Based on clinical and autopsy findings, she was diagnosed with acute respiratory failure due to pulmonary aspergillosis with acute fibrinous and organizing pneumonia. This is the first reported case of pulmonary aspergillosis with acute fibrinous and organizing pneumonia complicated by calcium oxalate resulting from Aspergillus niger infection, leading to severe inflammation and tissue injury in the lungs.